Synthesis of biomimetic monolithic biochar-based catalysts for catalytic decomposition of biomass pyrolysis tar. (1st May 2021) - Tian, Beile; Du, Shilin; Guo, Feiqiang; Dong, Yichen; Mao, Songbo; Qian, Lin; Liu, Qi
Abstract: Catalytic reforming of tar is an urgent technique for fuel gas production from biomass. In this paper, using monolith pinewood as the raw material, biomimetic monolithic biochar-based catalysts with the inherited 3D porous structure were prepared via simple impregnation and carbonization to explore their catalytic performance on biomass pyrolysis tar decomposition. Regular flow-through channels (20–50  μ m) were achieved in the axial direction of the catalysts with irregular pores in the cross direction. High-density and well-dispersed Ni 0 nanoparticles were formed and encapsulated on the wall of channels by in-situ reactions during biomass carbonization. The channels ensured the quick passing through of the gas flow and thus the diffusion steps could be effectively reduced, thereby reducing the coke deposition and aggregation of Ni particles. Based on their unique structure, the catalysts exhibited high activity and good stability for the biomass tar decomposition. At 800 °C, the catalyst (PC@0.3Ni) reached a high tar conversion of over 92% with excellent stability during five consecutive tests, leading to a higher yield of the product gas, especially the yields of H2 and CO. The distribution of Ni nanoparticles on the spent PC@0.3Ni was almost the same as the fresh catalyst with a similar particle size range. Highlights: Biomimetic monolithic char-based catalysts were synthesized for tar cracking. The biological structure of pinewood was well retained with regular channels. High-density and well-dispersed Ni NPs were encapsulated on the wall of channels. High performance on tar conversion was obtained to produce more H2 and CO. Excellent stability was achieved during the five times consecutive reuse.